2016
DOI: 10.1063/1.4939769
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of cyclohexane ion induced by intense femtosecond laser fields by ion-trap time-of-flight mass spectrometry

Abstract: Decomposition of cyclohexane cations induced by intense femtosecond laser fields at the wavelength of 800 nm is investigated by ion-trap time-of-flight mass spectrometry in which cyclohexane cations C6H12 (+) stored in an ion trap are irradiated with intense femtosecond laser pulses and the generated fragment ions are recorded by time-of-flight mass spectrometry. The various fragment ion species, C5Hn (+) (n = 7, 9), C4Hn (+) (n = 5-8), C3Hn (+) (n = 3-7), C2Hn (+) (n = 2-6), and CH3 (+), identified in the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The hydrogen migration process within a molecule in intense laser field has been an attractive research both theoretically and experimentally during the last several years . When irradiated with intense femtosecond laser pulses, neutral hydrocarbon molecules can experience dissociative ionization (DI) and Coulomb explosion (CE) processes in most cases, and intramolecular hydrogen migration processes are frequently observed among these two dynamical processes and are identified prior to skeletal bond breaking processes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen migration process within a molecule in intense laser field has been an attractive research both theoretically and experimentally during the last several years . When irradiated with intense femtosecond laser pulses, neutral hydrocarbon molecules can experience dissociative ionization (DI) and Coulomb explosion (CE) processes in most cases, and intramolecular hydrogen migration processes are frequently observed among these two dynamical processes and are identified prior to skeletal bond breaking processes .…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies of cyclohexane showed that cyclohexane can be extensively fragmented into a number of fragment ions (from CH n + to C 5 H m + ) under intense femtosecond laser field via DI and CE processes; the quantum chemical calculations of cyclohexane trication C 6 H 12 3+ illustrated a high mobility in highly charged cyclohexane cations . Yamanouchi and coworkers experimentally studied the decomposition of cyclohexane cation by ion‐trap time‐of‐flight (TOF) mass spectrometry . Their investigations showed that dissociation of cyclohexane cation proceeded by the photon irradiation, and the numbers of photons involved in the photon‐absorption processes were estimated.…”
Section: Introductionmentioning
confidence: 99%
“…One subject worth investigating is the correlation between the chemical reactivity and the charge number of MMCs. The thermal and photochemical reactions of cation radicals have been well explored . However, little is known about MMCs except dications .…”
Section: Introductionmentioning
confidence: 99%
“…The thermala nd photochemical reactions of cation radicals have been well explored. [16][17][18][19] However,l ittle is knowna bout MMCs except dications. [5,20] Since MMCs are metastable in nature, slow dissociation processes, namely,m etastable decays and/or post-source decays (PSDs), are expected to occurw hen sufficient internal energy is deposited on ap recursor MMC.…”
Section: Introductionmentioning
confidence: 99%